Assessment of stress distribution and pain perception in knife-edge ridge with different thicknesses of acrylic soft denture liner: A static linear three-dimensional finite element analysis - Coryniken, Siti; Nasution, Ismet Danial; Sabri, Muhammad; Ariyani, Ariyani (Edelweiss Applied Science and Technology, 2025)
Previous studies on stress distribution and pain perception in dentures with acrylic soft liners have focused solely on axial loading, neglecting the oblique forces involved in mastication. This study aimed to evaluate stress distribution and pain perception with varying acrylic liner thicknesses (1 mm, 2 mm, and 3 mm) under both axial and oblique loads. An in-silico study was performed employing static linear three-dimensional finite element analysis. The von Mises stress color contour plot was used to analyze stress distribution. The study found that without an acrylic soft denture liner, the highest stress distribution occurred at the anterior buccal shelf under axial load and at the posterior lingual vestibule under oblique load. With a 1 mm liner, peak stress was observed at the canine ridge crest under axial load and at the molar 3 ridge crest under oblique load. At 2 mm, peak stress was noted at the incisive ridge crest under axial load and at the molar 3 ridge crest under oblique load. With a 3 mm liner, peak stress distribution was found at the incisive ridge crest under axial load and at the retromolar pad area under oblique load. The 1 mm acrylic soft denture liner provides optimal comfort and pain reduction, effectively distributing stress in axial and oblique chewing loads, whereas thicker liners may reduce the denture’s ability to resist deformation, leading to higher stress distribution and discomfort.